Two new Cyrtodactylus (Squamata, Gekkonidae) from Northeast India - Purkayastha, Jayaditya; Lalremsanga, Hmar Tlawmte; Litho, Beirathie; Rathee, Yashpal Singh; Bohra, Sanath Chandra; Mathipi, Vabeiryureilai; Biakzuala, Lal; Muansanga, Lal (European Journal of Taxonomy, 2022)
We describe two new species of Cyrtodactylus Gray, 1827, each from the Indian states of Meghalaya and Mizoram based on morphology and ND2 gene sequences. The new species are a part of the Cyrtodactylus khasiensis group. Both species represent the highland clade within the south of Brahmaputra clade of Indo-Burmese Cyrtodactylus. Based on ND2 gene sequence, the species from Meghalaya have an uncorrected p-distance of 4.21%–4.25% from a lowland species C. guwahatiensis Agarwal, Mahony, Giri, Chaitanya & Bauer, 2018 and is a sister taxon to C. septentrionalis Agarwal, Mahony, Giri, Chaitanya & Bauer, 2018. The species from Mizoram differ from its sister species C. bengkhuaiai Purkayastha, Lalremsanga, Bohra, Biakzuala, Decemson, Muansanga, Vabeiryureilai, Chauhan & Rathee, 2021 by a p-distance of 8.33%.